Management of retrieval service patients within a paediatric emergency department. (20th October 2014) - Andrews, Sarah L; Lewena, Stuart; Oberender, Felix; Babl, Franz E; West, Adam; Hopper, Sandy M
Abstract Objective The Victorian Paediatric Emergency Transport Service (PETS) transports critically unwell children to tertiary paediatric hospitals. Children not directly admitted to ICU go to a tertiary ED. These patients might require prolonged and high‐level care. In light of the National Emergency Access Target, we describe this cohort, clinical care needs and process measures. Methods A retrospective chart review of patients retrieved by PETS to the Royal Children's Hospital (Melbourne, Australia) ED in 2012. Demographics, illness parameters and process measures were extracted. The ED length of stay (LOS) and time to ward suitability (time at which physiological parameters stabilised and high acuity treatments ceased) were related to patient and illness characteristics. Data are presented descriptively and analysed using spss. Results In 2012, 120 patients were transported to the ED. Conditions included lower respiratory (44), neurological (28), upper respiratory (16) and trauma (14). The median ED LOS was 4.8 h (interquartile range 2.9, 7.7). On arrival, 73 (60.8%) were ward‐suitable, but 51 (43%) had LOS less than 4 h. Twenty‐five (20.8%) patients stayed longer than 8 h. Administrative delay (principally bed block) is responsible for the bulk of the LOS; however, 25 (20.8%) had markedly abnormal vital signs after 4 h of ED care, mainly patients with lower respiratory tract disease. Conclusion Most patients retrieved to the ED ultimately go to a ward rather than ICU and most have an ED stay in excess of National Emergency Access Target. Several retrieval associated care issues, such as timely and appropriate ward disposition, can be addressed by administrative changes.